Reimagining Kangaroo Care for Preterm Infants: A Novel Garment for Safe and Comfortable Bonding - Alexandra McMillin; Aviva Presser Aiden; Jules P. Sherman; Ruth Ann Crystal; William D. Rhine (MDPI AG, 2024)
Background/Objectives: Kangaroo Care (KC) has been proven to enhance physiological stability, growth, and bonding in preterm, low-birthweight infants. Despite its benefits, KC is underutilized in Level IV Neonatal Intensive Care Units (NICUs) due to challenges in managing medical equipment. This study introduces the Kangarobe™, a novel garment designed to facilitate safe, comfortable, and efficient KC for medically fragile infants in high-acuity NICUs. Methods: From 2021 to 2023, a feasibility study was conducted involving 25 infant-parent dyads in a Level IV NICU. The Kangarobe™ was designed using human-centered design principles and tested on infants dependent on respiratory support. Surveys employing a 5-point Likert scale were administered to parents and nursing staff to assess safety, comfort, ease of use, and procedural access. Results: Survey results showed positive feedback from both parents and nursing staff, particularly in the areas of safety and comfort. For example, 72-80% of parents and nurses responded positively regarding ease and comfort. High level of agreement (76%) on the security of medical line management, with minimal negative feedback. In addition, parents using the Kangarobe™ held their infants for an average of 171 min per session, with a notable increase compared to the typical 75 min, indicating enhanced comfort and feasibility for extended KC sessions. The Kangarobe™ successfully enabled the secure management of medical lines and tubes, with the vertical access window improving procedural efficiency without interrupting KC. Conclusions: The Kangarobe™ demonstrates promise in addressing barriers to KC in high-acuity NICUs. By enhancing safety, comfort, and ease of use, it supports wider adoption of KC practices, potentially improving patient safety, staff efficiency, and family-centered care.